Prevalence and antimicrobial susceptibility of bacterial pathogens isolated from urine specimens received in rizgary hospital — Erbil. Issue 3 (May 2019) - Al-Naqshbandi, Ahmed A.; Chawsheen, Mahmoud A.; Abdulqader, Haval H.
Abstract: Background: Urinary tract infection (UTI) is a common health-associated problem worldwide. Like other medical conditions, UTI patients may suffer from poor treatment outcomes due to the emergence of antimicrobial resistance. Determining patterns of antimicrobial susceptibility in uropathogens will guide physicians to choose the best antibiotics for treating affected patients. In this project we aimed to evaluate the frequencies of pathogens associated with UTI and their antimicrobial susceptibility patterns. Methods: This study was conducted on 2692 urine samples of patients visited Rizgary Teaching Hospital in Erbil city. Aerobic bacterial growth identification and antimicrobial susceptibility tests were performed using VITEK ® 2 compact system. Results: Our data show that more than 20% of all studied samples were negative for bacterial growth; only 16.72% of them were pathogenic bacteria in which 82.44% of them were Gram negative bacteria (GNB) and the rest were Gram positive bacteria (GPB). Escherichia coli was the most frequent, and Acinetobacter baumannii was the most resistant GNB. Staphylococcus haemolyticus was the most frequent, and Enterococcus faecalis was the most resistant GPB. In general GNB were highly resistant to Ticarcillin and Cefepime, and GPB were also resistant to Ticarcillin, and Tigecycline antibiotics. Conclusions: The amount of negative culture growth indicates that symptoms only based diagnosis for UTI detection is unreliable. E. coli is the most UTI related pathogen, E. faecalis and A. baumannii were among highly antibiotic resistant bacteria. Finally, since many of GNG and GPB isolates were resistant to several antibiotics, there might be a high possibility for multi drug resistant among local population in Erbil.